Particulate matter combustion catalyst
By concentrating Sr on the surface of Zr-based composite oxide particles within specific concentration and surface area limits, the catalyst's combustibility and durability are enhanced, addressing deliquescence issues and improving particulate matter removal efficiency.
Patent Information
- Application Number
- JP2021075194
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-04-27
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2041-04-27
AI Technical Summary
The deliquescence of Sr compounds on the surface of Zr-based composite oxides used as particulate matter combustion catalysts due to water vapor in exhaust gas leads to catalyst poisoning and loss, limiting the efficiency and durability of particulate matter removal systems.
Concentrating Sr on the surface of Zr-based composite oxide primary particles while controlling the amount of solid solution to 1.2% by mass or less, with a surface concentration of 2.4-2.8 mol% Sr, enhances oxygen ion conductivity and promotes the release of highly active oxygen, improving combustibility without deliquescence issues.
The controlled Sr concentration and specific surface area of the catalyst enhance oxygen ion conductivity, leading to improved particulate matter combustion efficiency and catalyst durability, despite reduced specific surface area, thereby maintaining effective particulate matter removal.
Smart Images

Figure 0007615868000002 
Figure 0007615868000003 
Figure 0007615868000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a particulate matter combustion catalyst for combusting particulate matter contained in engine exhaust gas. [Background technology]
[0002] In diesel engine vehicles, a catalyst for burning particulate matter (PM) contained in exhaust gas may be installed in the DPF (diesel particulate filter). Also, in gasoline engine vehicles, particularly in direct injection gasoline engines, the fuel becomes too rich near the spark plug, generating smoke, so a GPF (gasoline particulate filter) with a catalyst may be installed to burn and remove the particulate matter associated with this smoke.
[0003] Patent Document 1 describes the use of a Sr-doped Zr-based composite oxide, which is a ZrNd composite oxide with Sr dissolved therein, as a catalyst for burning the particulate matter. Zr-based composite oxides are known to have oxygen ion conductivity, which allows oxygen ions to move from a high oxygen concentration area to a low oxygen concentration area. Oxygen is released from the particle surface due to this oxygen ion conductivity, and the oxygen contributes to the combustion of the particulate matter. The dissolution of Sr in this Zr-based composite oxide increases the number of oxygen vacancies (atomic vacancies), thereby increasing the oxygen ion conductivity. Patent Document 1 exemplifies a Sr-doped Zr-based composite oxide with a composition of SrO:ZrO2:Nd2O3=1.9:86.6:11.5 (molar ratio).
[0004] Patent Document 2 describes a method in which a mixed aqueous solution of 0.0924 mol of zirconium oxychloride, 0.0038 mol of lanthanum nitrate, and 0.0036 mol of strontium nitrate is dropped into an alkaline aqueous solution to obtain a coprecipitate, which is then dried and fired at 650° C. for 3 hours to prepare a ZrLaSr composite oxide, and which is then impregnated with Rh to obtain a catalyst for purifying exhaust gas. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent No. 5942550 [Patent Document 2] JP 2006-169035 A Summary of the Invention [Problem to be solved by the invention]
[0006] To burn off the particulate matter that has accumulated on the filter, it is necessary to raise the temperature of the filter by increasing the exhaust gas temperature. Increasing the temperature of the exhaust gas increases the amount of fuel consumed by the engine. To avoid a deterioration in the fuel efficiency of the engine, it is necessary to shorten the time required to burn off the particulate matter, that is, to increase the burning speed of the particulate matter.
[0007] In the above-mentioned Sr-doped Zr-based composite oxide, the more the amount of Sr dissolved in the solid solution, the more oxygen vacancies there are, and the better the oxygen ion conductivity becomes. Therefore, it is considered that increasing the amount of Sr dissolved in the Zr-based composite oxide is effective in improving the burning rate.
[0008] However, there is a limit to the amount of Sr that can be dissolved in Zr-based composite oxides, and the Sr that cannot be dissolved exists alone as a compound (mainly strontium carbonate) on the particle surface of the composite oxide. This Sr compound has deliquescent properties. This causes the problem of deliquescence of the Sr compound due to water vapor in the exhaust gas that flows into the filter that captures particulate matter. The problem is that the Sr compound dissolves due to the water vapor that flows into the filter, poisoning the Zr-based composite oxide itself, and if the filter supports another catalyst, the catalyst will be poisoned. Furthermore, there is the problem that the deliquescent Sr compound flows out of the filter.
[0009] An object of the present invention is to improve the combustibility of particulate matter without inviting the problem of deliquescence of Sr compounds when a Sr-doped Zr-based composite oxide is used as a particulate matter combustion catalyst. [Means for solving the problem]
[0010] In order to solve the above problems, the present invention is directed to concentrating Sr on the surfaces of primary particles of the Zr-based composite oxide while suppressing the amount of Sr dissolved in the Zr-based composite oxide.
[0011] The particulate matter combustion catalyst disclosed herein is a catalyst for burning particulate matter contained in engine exhaust gas, Sr-doped Zr-based composite oxide formed by dissolving Sr in Zr-based oxide and a precious metal as a catalytic metal. Contains The Sr-doped Zr-based composite oxide contains Zr, Nd, Pr and Sr, The Sr-solid-solubilized Zr-based composite oxide has a Sr solid-solubilized amount of 1.2 mass % or less, At least a portion of the primary particles of the Sr-doped Zr-based composite oxide is characterized in that the Sr concentration in all metal elements on the particle surface is 2.4 mol % or more and 2.8 mol % or less, as measured by surface analysis using X-ray photoelectron spectroscopy.
[0012] According to this, the amount of Sr dissolved in the Sr-doped composite oxide is 1.2 mass% or less, so that the problem of Sr compounds being deliquesced by water vapor on the particle surface of the Zr-based composite oxide can be avoided. And the Sr concentration on the particle surface of the Sr-doped Zr-based composite oxide is 2.4 mol% or more and 2.8 mol% or less means that the Sr concentration near the particle surface is higher than that inside the particle, that is, there are many oxygen defects near the particle surface, and oxygen ion conductivity is high. Therefore, the intake of oxygen from the outside, the movement of lattice oxygen from the inside of the particle to the particle surface, and the release of highly active oxygen from the particle surface are promoted, improving the combustibility of the particulate matter.
[0013] In one embodiment, the specific surface area of the Sr-doped Zr-based composite oxide is 40 m 2 / g or more 75m 2 / g or less.
[0014] Generally, the larger the specific surface area of the catalyst, the easier it is to come into contact with particulate matter, and the better the combustibility of the particulate matter. In contrast, in the case of the Sr-doped Zr-based composite oxide according to the present invention, as will be described in the examples below, the specific surface area is 40 m 2 / g or more 75m 2 Although the particle size is small (less than 1 / g), it has the characteristic of having good combustibility.
[0015] The above-mentioned concentration of Sr on the particle surface can be achieved by increasing the calcination temperature during preparation of the Sr-doped Zr-based composite oxide, and the higher the calcination temperature, the greater the concentration of Sr on the surface, while the smaller the specific surface area of the resulting Sr-doped Zr-based composite oxide becomes. This means that the surface concentration of Sr exceeds the decrease in combustibility of the particulate matter due to the smaller specific surface area, and the improvement in said combustibility occurs as a result of the surface concentration of Sr.
[0016] By increasing the calcination temperature, it is possible to increase the Sr concentration on the particle surface above 2.8 mol%, but the associated decrease in the specific surface area leads to an increase in the hardness of the composite oxide. If the hardness increases, it becomes difficult to crush the catalyst, which hinders the formation of a slurry when coating the catalyst on a support. Therefore, the Sr concentration on the particle surface should be kept below 2.8 mol% (the specific surface area is 40 m 2 / g or more).
[0017] above The Sr-doped Zr-based composite oxide contains Zr, Nd, and Sr. In this case, it is believed that the interaction between divalent Sr, tetravalent Zr, and trivalent Nd in the vicinity of the surface of the primary particles of the composite oxide promotes the movement of lattice oxygen, which leads to improved combustibility of particulate matter. In one embodiment, the particulate matter combustion catalyst comprises activated alumina having the above-mentioned precious metal supported thereon.
[0018] aboveThe Sr-doped Zr-based composite oxide contains Zr, Nd, Pr, and Sr. In this case, it is believed that the interaction between divalent Sr and tetravalent Zr, trivalent Nd, and trivalent or tetravalent Pr near the surface of the primary particles of the composite oxide promotes the movement of lattice oxygen, which leads to improved combustibility of particulate matter.
[0019] In one embodiment, the Sr-doped Zr-based composite oxide has the above A precious metal is supported on the catalyst. Therefore, the combustion of particulate matter by the precious metal is promoted by the highly active oxygen released from the Sr-doped Zr-based composite oxide. As the precious metal, it is preferable to adopt Pt and / or Pd. Effect of the Invention
[0020] According to the present invention, the amount of Sr dissolved in the Sr-dissolved Zr-based composite oxide is 1.2 mass% or less, and at least a portion of the primary particles of this Sr-dissolved Zr-based composite oxide has a Sr concentration of 2.4 mol% or more and 2.8 mol% or less of all metal elements on the particle surface, as measured by surface analysis using X-ray photoelectron spectroscopy, so that the combustibility of particulate matter can be improved without incurring the problem of deliquescence of Sr compounds. [Brief description of the drawings]
[0021] [Figure 1] FIG. 1 is a diagram showing a state in which a DPF is disposed in an exhaust gas passage of an engine. [Diagram 2] FIG. 2 is a front view showing a schematic diagram of the DPF. [Diagram 3] FIG. 2 is a vertical cross-sectional view showing a schematic diagram of a DPF. [Figure 4] 2 is an enlarged cross-sectional view showing a schematic diagram of a wall separating an exhaust gas inlet passage and an exhaust gas outlet passage of the DPF. FIG. [Diagram 5] 1 is a micrograph of a particulate matter combustion catalyst. [Figure 6] FIG. 2 is an explanatory diagram showing the transfer of oxygen when particulate matter is combusted in a particulate matter combustion catalyst. [Figure 7]1 is a graph showing the relationship between the Sr concentration of a Sr-doped Zr-based composite oxide, the carbon combustion time, and the specific surface area. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] Hereinafter, the embodiments of the present invention will be described with reference to the drawings. The following description of the preferred embodiments is merely illustrative in nature and is not intended to limit the present invention, its application, or its uses.
[0023] The particulate matter combustion catalyst (hereinafter simply referred to as the "combustion catalyst") according to this embodiment is supported on a DPF 1 shown in Fig. 1. In the figure, reference numeral 11 denotes an exhaust passage of a diesel engine. The DPF 1 is provided in this exhaust passage 11.
[0024] An oxidation catalyst (not shown) made of a support material such as activated alumina carrying a catalytic metal such as Pt or Pd can be disposed in the exhaust passage 11 upstream of the DPF1 in the exhaust gas flow. When such an oxidation catalyst is disposed upstream of the DPF1, the oxidation catalyst oxidizes HC and CO in the exhaust gas, and the heat of the reaction increases the exhaust gas temperature to heat the DPF1, thereby burning and removing particulate matter. In addition, NO in the exhaust gas is oxidized to NO2 by the oxidation catalyst, and the NO2 is supplied to the DPF1 as an oxidizing agent for burning particulate matter.
[0025] As shown typically in Figures 2 and 3, the DPF 1 has a honeycomb structure and includes a large number of exhaust gas passages 2, 3 extending parallel to one another. That is, the DPF 1 has exhaust gas inlet passages 2 whose downstream ends are blocked by plugs 4 and exhaust gas outlet passages 3 whose upstream ends are blocked by plugs 4, arranged alternately. The exhaust gas inlet passages 2 and the exhaust gas outlet passages 3 are separated by a thin partition wall 5. Note that the hatched portion in Figure 2 indicates the plugs 4 at the upstream ends of the exhaust gas outlet passages 3.
[0026] DPF1 is formed of an inorganic porous material such as cordierite, SiC, Si3N4, or sialon. The exhaust gas flowing into the exhaust gas inflow passage 2 flows out into the adjacent exhaust gas outflow passage 3 through the surrounding partition walls 5 as indicated by the arrows in FIG. 3. As shown in FIG. 4, the partition wall 5 has minute pores (exhaust gas passages) 6 that communicate the exhaust gas inflow passage 2 and the exhaust gas outflow passage 3, and the exhaust gas passes through these pores 6. The particulate matter is mainly captured and deposited on the walls of the exhaust gas inflow passage 2 and the pores 6.
[0027] A catalyst layer 7 containing the combustion catalyst is formed on the wall surface that forms the exhaust gas passages (the exhaust gas inflow passage 2, the exhaust gas outflow passage 3, and the pores 6) of the DPF1 as the carrier substrate. Note that it is not always necessary to form the catalyst layer on the wall surface on the exhaust gas outflow passage 3 side. The combustion catalyst uses Sr solid-solution Zr-based composite oxide particles, and the main component metal element is Zr.
[0028] The Sr solid-solution Zr-based composite oxide particles referred to here are secondary particles formed by aggregation of a large number of Sr solid-solution Zr-based composite oxide primary particles 12, as shown in FIG. 5. In the figure (photograph), a lump in which a large number of small particles overlap is shown, and each of the small particles is the primary particle 12, and the lump is the secondary particle.
[0029] In addition to the Sr solid-solution Zr-based composite oxide particles, other combustion catalysts such as noble metal-supported activated alumina may be added to the catalyst layer. Also, noble metals may be supported on the Sr solid-solution Zr-based composite oxide particles.
[0030] <Regarding Sr Solid-Solution Zr-Based Composite Oxides> The Sr solid-solution Zr-based composite oxide is a composite oxide in which Sr is solid-solved in a Zr-based oxide. The Zr-based oxide may be zirconia or a composite oxide of Zr and a rare earth element. For example, ZrNd composite oxide and ZrNdPr composite oxide are preferable. In the case of this composite oxide, the main component is Zr.
[0031] The amount of Sr dissolved in the Sr-doped Zr-based composite oxide is preferably 1.2 mass% or less. Even if the Sr-doped Zr-based composite oxide is prepared by adjusting the amount of raw materials charged so that the amount of Sr dissolved is more than 1.2 mass% by coprecipitation, some of the Sr does not dissolve in the composite oxide and precipitates on the particle surface as a carbonate compound. Such strontium carbonate deliquesces due to water vapor in the exhaust gas, causing poisoning of other catalyst components or leaking out of the DPF.
[0032] The Sr-doped Zr-based composite oxide preferably has a Sr concentration of 2.4 mol% or more and 2.8 mol% or less in the total metal elements on the primary particle surface, as measured by surface analysis using XPS (X-ray photoelectron spectroscopy). According to literature surveys and experiments by the present inventors, the Sr concentration on the primary particle surface of conventional Sr-doped Zr-based composite oxides is about 2 mol% (at most about 2.2 mol%). In contrast, the Sr-doped Zr-based composite oxide according to the present invention has a Sr concentration of 2.4 mol% or more, so that there are many oxygen defects 13 near the surface of the primary particles 12, as shown in FIG. 6. Therefore, oxygen ion conduction promotes the intake of oxygen from the outside, the movement of lattice oxygen from the inside of the particles to the particle surface, and the release of highly active oxygen from the particle surface, thereby improving the combustibility of particulate matter (soot, etc.) 14.
[0033] <Example> -Preparation of Sr-doped Zr-based composite oxide- Zirconyl nitrate, neodymium nitrate, praseodymium nitrate, and strontium nitrate were each dissolved in ion-exchanged water, and these aqueous solutions were mixed. The resulting mixed solution (acidic solution) was mixed with an 8-fold dilution of 28% by mass ammonia water as a basic solution to neutralize it, obtaining a coprecipitate (a precursor of a complex oxide of Zr, Nd, Pr, and Sr). The solution containing this coprecipitate was centrifuged to remove the supernatant (dehydration), and then ion-exchanged water was added thereto and stirred (water washing). By repeating this dehydration and water washing operation as many times as necessary, the excess basic solution was removed. The dehydrated coprecipitate was then dried overnight in the air at a temperature of 150°C, crushed, and then fired in the air at temperatures of 500°C, 650°C, 670°C, 700°C, 750°C, and 800°C for 2 hours, to obtain each Sr-doped Zr-based complex oxide fired at different temperatures.
[0034] The composition of each Sr-doped Zr-based composite oxide is ZrO2:Nd2O3:Pr6O 11 The molar ratio of Sr to SrO was 77:13:7:3, and the amount of Sr in solid solution was 1.2 mass %.
[0035] As the Zr source, Nd source, Pr source and Sr source, for example, acetates can be used, and as the basic solution, for example, other solutions such as an aqueous sodium hydroxide solution can also be used.
[0036] -Sr concentration and specific surface area of Sr-doped Zr-based composite oxides- The Sr concentration (measured by XPS) on the primary particle surface and the specific surface area of the secondary particles of each Sr-doped Zr-based composite oxide with different firing temperatures are shown in Table 1. The conditions for measuring the Sr concentration by XPS are as follows:
[0037] X-ray source: AlKα radiation Detection area: 30μmφ Detection depth: 1~2nm Focusing on four peaks of the 3d orbitals of Zr, Nd, Pr and Sr in the XPS spectrum, the Sr concentration was calculated from the ratio of these peak intensities.
[0038] According to Table 1, the higher the firing temperature, the higher the Sr concentration and the smaller the specific surface area.
[0039] [Table 1]
[0040] -Evaluation of catalysts for particulate matter combustion- The above Sr-doped Zr-based composite oxides with different Sr concentrations and specific surface areas were mixed with Pt-Pd / Al2O3 catalyst powder. Each mixed powder was mixed with binder and ion-exchanged water, and pulverized in a ball mill to prepare a slurry. Each slurry was coated onto a DPF, which was then dried (150°C) and fired (held at 500°C in air for 2 hours) to prepare DPFs with each catalyst for evaluation.
[0041] The Pt-Pd / Al2O3 catalyst powder was prepared by supporting Pt and Pd on activated alumina by the evaporation-to-dryness method. Dinitrodiamineplatinum(II) nitric acid solution was used as the Pt source, and palladium(II) nitrate solution was used as the Pd source.
[0042] The DPF used was a SiC honeycomb filter (volume 11 mL) with a cell wall thickness of 16 mil (4.064 x 10-1 mm) and 178 cells per square inch (645.16 mm2). The amount of Sr-doped Zr-based composite oxide supported per liter of DPF was 15 g / L, and the amount of Pt-Pd / Al2O3 catalyst powder supported was 10.2 g / L.
[0043] Then, 5g / L of carbon was deposited as particulate matter on the exhaust gas passage wall of each catalyst-equipped DPF. Each catalyst-equipped DPF was attached to a simulated gas flow reactor and heated to 640°C in an N2 atmosphere. After the DPF inlet temperature stabilized at 640°C, simulated exhaust gas (O2: 7%, NO: 300ppm, remaining N2) was flowed at a space velocity of 40,000 / h, and the concentrations of CO and CO2 generated by carbon combustion were measured in real time. Then, based on the CO and CO2 concentrations, the carbon combustion rate was calculated using the following formula, and the cumulative value of the amount of carbon burned per second was calculated from this, and the combustion time required for 50% carbon to be burned was calculated.
[0044] Carbon Burn Rate (g / h) = {Gas flow rate (L / h) × [(CO+CO2) concentration (ppm) / (1 × 106)]} × 12 (g / mol) / 22.4 (L / mol) The results are shown in Table 1 and Figure 7. Looking at the relationship between the specific surface area and the carbon combustion time in Figure 7, the smaller the specific surface area, the shorter the carbon combustion time, that is, the better the carbon combustion properties. This tendency deviates from the general rule (the larger the specific surface area of a solid catalyst, the larger the contact area with the reactants, and therefore the more efficient the catalytic reaction), and is the opposite tendency. This is because, as can be seen from the graph showing the relationship between the specific surface area and the Sr concentration in Figure 7, the smaller the specific surface area, the higher the Sr concentration. In other words, it is recognized that the Sr concentration on the primary particle surface of the Sr-doped Zr-based composite oxide is higher, and oxygen defects in the vicinity of the particle surface increase, improving oxygen ion conductivity, and thus improving the carbon combustion properties. According to Table 1 and Figure 7, when the Sr concentration is 2.4 mol% or more (specific surface area is 71 m), the carbon combustion time is shorter, that is, the better the carbon combustion properties. 2 / g or less), the carbon burn time is 80 seconds or less.
[0045] According to the general rule above, the larger the specific surface area, the better. 2 / g.
[0046] As is clear from Table 1, the higher the calcination temperature during preparation of the Sr-doped Zr-based composite oxide, the higher the Sr concentration. It is therefore possible to increase the Sr concentration above 2.8 mol%, but the associated decrease in specific surface area leads to an increase in hardness of the composite oxide. If the hardness increases, it becomes difficult to pulverize the catalyst, which hinders the formation of a slurry when coating the catalyst on a support. Therefore, the Sr concentration should be 2.8 mol% or less (the specific surface area is 40 m 2 / g or more).
[0047] It should be noted that, although the above embodiment is an example in which the particulate matter combustion catalyst according to the present invention is supported on a DPF, this catalyst can also be supported on a GPF and placed in the exhaust gas passage of a direct injection type gasoline engine in order to be used for burning and removing particulate matter contained in the exhaust gas of the gasoline engine. [Explanation of symbols]
[0048] 1 DPF 2 Exhaust gas inlet (exhaust gas passage) 3 Exhaust gas outlet (exhaust gas passage) 6 Pore (exhaust gas passage) 7 Catalyst layer 11 Exhaust passage 12 Primary particles 13 Oxygen vacancies 14 Particulate matter
Claims
1. A particulate matter combustion catalyst for combusting particulate matter contained in an exhaust gas of an engine, comprising: The present invention comprises a Zr-based composite oxide having a solid solution of Sr in a Zr-based oxide, and a precious metal as a catalytic metal, The Sr-doped Zr-based composite oxide contains Zr, Nd, Pr and Sr, The Sr-solid-solution Zr-based composite oxide has a Sr solid-solution amount of 1.2 mass% or less, A particulate matter combustion catalyst characterized in that at least a portion of the primary particles of the Sr-doped Zr-based composite oxide has a Sr concentration of 2.4 mol% or more and 2.8 mol% or less in all metal elements on the particle surface, as measured by surface analysis using X-ray photoelectron spectroscopy.
2. In claim 1, The specific surface area of the Sr-doped Zr-based composite oxide is 40 m 2 / g or more 75m 2 / g or less.
3. In claim 1 or 2, A particulate matter combustion catalyst comprising the above-mentioned activated alumina carrying a noble metal.
4. In claim 1 or 2, A particulate matter combustion catalyst comprising the above-mentioned Sr-doped Zr-based composite oxide carrying the above-mentioned noble metal.
Citation Information
Patent Citations
Image processing device
JP1984042550A
Heat resistant oxide
JP2006169035A
Inorganic mixed oxide and exhaust gas purification catalyst using the same
JP2009107901A
Catalyst for burning particulate matter
JP2013059759A
Particulate filter with catalyst, and production method of the same
JP2016043323A